Opportunities and Challenges for Establishing a Resource Nexus Community of Science and Practice - Mohtar, Rabi H.; Sharma, Virender K.; Daher, Bassel; Laspidou, Chrysi; Kim, Hyunook; Pistikopoulos, Efstratios N.; Nuwayhid, Iman; Lawford, Richard; Rhouma, Ali; Najm, Majdi Abou (Frontiers in Environmental Science, 2022)
The American Chemical Society’s Division of Environmental Chemistry symposium Toward Creating a Water-Energy-Food (WEF) Nexus Community of Practice, brought together 25 cross-disciplinary speakers in five thematic areas: 1) state of the art models and approaches, 2) WEF Nexus initiatives and case studies, 3) WEF governance and stakeholder engagement, 4) chemical processes and WEF Nexus, 5) WEF education, community, and practice. Discussions included diverse perspectives from different areas of expertise and provided key take-home messages toward building a WEF community of practice. This paper summarizes those messages, drawing conclusions regarding the anticipated challenges and opportunities moving toward establishing a resource-nexus community of science and practice that includes the chemical societies. We define the community of science and practice as a bottom-up approach of formal and non-formal scientists, policy makers, practitioners, technology providers, and civil society members concerned with any aspect of water, energy, food, ecosystem resources allocation, management, governance, and financing. The roles of chemistry and chemical processes in understanding the interlinkages of nexus systems must not be overlooked. Chemistry plays an important role in the circularity of the food and agriculture system, and in providing cleaner energy, cleaner water, and more sustainable food production. The question is how to better engage the chemical society in the WEF nexus moving forward? The paper proposes the resource of health, highlighting major challenges and opportunities in the Water-Energy-Food-Health-Ecosystems (WEFH) Nexus, and highlights future steps for fostering dialogue among this broad, multidisciplinary, multi-stakeholder community toward establishing an inclusive community of science and practice.